The Influence of Good Governance on the Financial Performance of the Central Government - Suprianto, Agung; Saputri, Yulia; Anabella, Anabella; Setyaningrum, Wahyuni Dwi Febriana; Aulia, Cika (Jurnal Multidisiplin Sahombu, 2025)
This study examines the influence of Good Governance on the financial performance of the central government in Indonesia. Good Governance, emphasizing transparency, accountability, participation, and responsibility, is believed to enhance the effectiveness and efficiency of public financial management. The study’s findings indicate that government institutions that consistently apply Good Governance principles tend to achieve better financial performance, particularly through more efficient and effective budget management. Furthermore, active public participation in decision-making processes is shown to strengthen public trust, positively influencing financial outcomes. The study highlights the critical role of Good Governance in optimizing public sector financial management. It recommends enhancing government employee competencies through training and capacity building in Good Governance practices. Additionally, it stresses the importance of formulating policies that encourage greater public involvement in governance processes. By applying these recommendations, it is expected that the financial performance of the central government will continue to improve, supporting broader objectives of accountability and public service quality. The study’s findings are intended to serve as a valuable reference for policymakers committed to strengthening financial governance and ensuring more sustainable and transparent public financial management in Indonesia.